Teun A. Van Dijk's Discourse Dimensions in Seno Gumira Ajidarma's Short Story Sepotong Senja Untuk Pacarku - Yunarius Ugi Suharjo; Anwar Efendi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to describe the dimensions of discourse in the short story Sepotong Senja Untuk Pacarku by Seno Gumira Ajidarma. Descriptive qualitative research method with critical discourse analysis approach of Teun A. Van Dijk model is used to develop this research. The results show that the text dimension, social cognition dimension, and social context dimension are contained in the short stories studied. The text dimension in the short stories consists of macro structure, superstructure, and micro structure. In the macro structure, the theme raised is about 'romance'. The superstructure and microstructure contain six elements and four elements respectively. The findings of the social cognition dimension are that the author wants to convey to readers that the development of technology today causes letters to no longer be an alternative to long-distance communication. The author also illustrates to the current generation how valuable and interesting it is to send and communicate through letters. The finding of the social context dimension is that the author wants readers to take concrete actions to prove what is expressed. The author also wants everyone to be able to accept and hear input or criticism from others